Current Genetic Testing Tools in Neonatal Medicine - Seema R. Lalani (Elsevier, 2017)
With the growing understanding of the magnitude of genetic diseases in newborns and equally rapid advancement of tools used for genetic diagnoses, healthcare providers must have a sufficient knowledge base to both recognize and evaluate genetic diseases in the neonatal period. Genetic assessment has become an essential aspect of medicine, and professionals need to know when genetic evaluation is indispensable. Much progress has been made in recent years in utilizing massively parallel sequencing for rapid diagnosis of genetic conditions in neonates. Next-generation sequencing is increasingly being used for noninvasive prenatal diagnosis, and it may become an essential component of newborn screening. This review will define some basic genetic terms and concepts, explain the gamut of genetic testing available for early diagnosis of genetic diseases, and describe some common chromosomal abnormalities, genomic disorders, and single-gene diseases relevant to neonatal medicine.